2015
DOI: 10.1039/c5ra15562b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of silicate sol–gel host matrices and catalyst agents on the luminescent properties of Eu3+/Gd3+ under different excitation wavelengths

Abstract: Sol–gel silicate glasses co-doped with Gd3+ and Eu3+ ions were successfully obtained and the pronounced effect of the matrix composition on the luminescent properties and energy transfer process from Gd3+ to Eu3+ was confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 56 publications
(77 reference statements)
0
11
0
Order By: Relevance
“…The sol-gel (SG) route appears to be a promising alternative to prepare OxGC films and bulk materials for different applications, such as planar waveguides or integrated optics [21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36]. Ballato et al [35] proposed to use LaF 3 into planar photonic devices, such as planar confined waveguide and Kumar et al [36] described Er 3+ doped LaF 3 transparent gels for its use in the infrared (IR) waveguide amplifiers at 1.5 μm.…”
Section: Introductionmentioning
confidence: 99%
“…The sol-gel (SG) route appears to be a promising alternative to prepare OxGC films and bulk materials for different applications, such as planar waveguides or integrated optics [21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36]. Ballato et al [35] proposed to use LaF 3 into planar photonic devices, such as planar confined waveguide and Kumar et al [36] described Er 3+ doped LaF 3 transparent gels for its use in the infrared (IR) waveguide amplifiers at 1.5 μm.…”
Section: Introductionmentioning
confidence: 99%
“…Results confirmed that GdF 3 NCs, 5 nm in size, precipitated during heat treatment at 300 and 400 °C, Figure 5, but GdOF NCs appeared when the temperature was increased to 500 °C. More recently, Szpikowska-Sroka et al studied the optical properties of Eu 3+ -doped SiO 2 -GdF 3 GCs, with a very low composition of active media, around 3–6 mol %, based on Fuhijara’s synthesis [65,66,67]. The PL associated with Eu 3+ ions in GdF 3 phase was more efficient due to the low phonon energy of the crystal phase.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the numerous optical materials are utilizing the luminescence from trivalent rare‐earth elements (RE 3+ ) . Hence, much research attention has been paid to the synthesis of RE 3+ ‐doped AF 3 nanocrystalline fluoride systems: LaF 3 , GdF 3 , and YF 3 .…”
Section: Introductionmentioning
confidence: 99%